117k views
3 votes
Solve the equation using the quadratic formula.
x^2 + 2x - 3

User TNR
by
4.9k points

2 Answers

5 votes

x²+2x-3

x²+3x-x-3

x(x+3)-1(x+3)

(x+3)(x-1)

x=-3,1

User Jefflovejapan
by
5.2k points
3 votes

Answer:

Explanation:

The given quadratic equation is expressed as

x² + 2x - 3 = 0

The equation is already in the standard form of ax² + bx + c

The general formula for solving quadratic equations is expressed as

x = [- b ± √(b² - 4ac)]/2a

From the equation given,

a = 1

b = 2

c = - 3

Therefore,

x = [- 2 ± √(2² - 4 × 1 × - 3)]/2 × 1

x = [- 2 ± √(4 - - 12)]/2

x = [- 2 ± √16]/2

x = (- 2 + 4)/2 or x = (- 2 - 4)/2

x = 2/2 or x = - 6/2

x = 1 or x = - 3

User FatFingers
by
4.8k points